JUN is a key transcriptional regulator of the unfolded protein response in acute myeloid leukemia - Zhou, Chao; Scholl, Claudia; Fröhling, Stefan (Leukemia, 2017)
The transcription factor JUN is frequently overexpressed in multiple genetic subtypes of acute myeloid leukemia (AML); however, the functional role of JUN in AML is not well defined. Here we report that short hairpin RNA (shRNA)-mediated inhibition of JUN decreases AML cell survival and propagation in vivo. By performing RNA sequencing analysis, we discovered that JUN inhibition reduces the transcriptional output of the unfolded protein response (UPR), an intracellular signaling transduction network activated by endoplasmic reticulum (ER) stress. Specifically, we found that JUN is activated by MEK signaling in response to ER stress, and that JUN binds to the promoters of several key UPR effectors, such as XBP1 and ATF4, to activate their transcription and allow AML cells to properly negotiate ER stress. In addition, we observed that shRNA-mediated inhibition of XBP1 or ATF4 induces AML cell apoptosis and significantly extends disease latency in vivo tying the reduced survival mediated by JUN inhibition to the loss of pro-survival UPR signaling. These data uncover a previously unrecognized role of JUN as a regulator of the UPR as well as provide key new insights into the how ER stress responses contribute to AML and identify JUN and the UPR as promising therapeutic targets in this disease.